The Influence of the Quranic STEM Approach on Da'wah Development in the Digital Era - Ranawigena, Ghaitsa; Anggrayni, Dewi (Jurnal Dakwah Risalah, 2023)
Science, Technology, Engineering, and Mathematics (STEM) are included in the Qur'an, so they can be called Quranic STEM (Q-STEM). The purpose of the study is to find out how Quranic STEM has an influence on da'wah development in the digital era. The research method used is quantitative, with the Kolmogorov-Smirnov normality test (K-S) precondition test and the Levene homogeneity test with Cronbach's Alpha threshold value, as well as hypothesis testing with the t test. The study was conducted on the student population of the Campus Da'wah Institute (LDK) at IPB University with a purposive sampling of as many as 84 people. The results of the normality test found that the Q-STEM variable got a sig value of 0.20 > 0.05 and the digital era da'wah variable 0.20 > 0.05, so that the data was normally distributed. Then, the homogeneity test results were obtained at 0.071 > 0.05, so the data was homogeneous. The results of the t-test hypothesis test were obtained at 0.00 < 0.01, indicating that the research found that Q-STEM had a significant influence on the development of da'wah in the digital era.